Pengaruh Kompetensi dan Disiplin Terhadap Kinerja Pegawai Dimediasi oleh Kepuasan Kerja Pada Badan Penanggulangan Bencana Daerah Kota Tidore Kepulauan - Abdullah, Suryani; Sabuhari, Rahmat; Alhadar, Fadhliah (EDUKASI, 2024)
One of the most important assets in an organization or company is human resources who will later become workers in an agency. This is due to its role as the subject of implementing policies and operational activities of an organization and company. The better the performance of the workforce, the better it can provide optimal results for an organization or company. In order to obtain optimal performance, good management is needed so that the workforce in an organization feels comfortable in carrying out their responsibilities and obtains maximum results. Considering the importance of employee performance in order to achieve workplace agency goals optimally, this encourages researchers to study in more depth academically the influence of employee competency and discipline variables on employee performance through job satisfaction at BPBD Tidore Islands City. Hypothesis 1 states that competence has a positive and significant effect on performance. Hypothesis 1 is accepted. Hypothesis 2 states that discipline has a positive and significant effect on performance so that hypothesis 2 is accepted. Hypothesis 3 competence has a positive and significant effect on job satisfaction so that hypothesis 3 is accepted. Hypothesis 4 work discipline has a positive and significant effect on job satisfaction so that hypothesis 4 is accepted. Hypothesis 5 job satisfaction does not affect employee performance so hypothesis 5 is rejected. Hypothesis 6 competency has no significant effect on performance if it is mediated by job satisfaction so hypothesis 6 is rejected. Hypothesis 7 work discipline has no significant effect on performance if it is mediated by job satisfaction so hypothesis 7 is rejected.